Idntificaion activity compounds as use GC-MS in essential oil from Thyme (Thymus vulgaris) and Star anise (Illicum verum) and Study the Inhibitory Activity of Against many pathogenic Bacteria - كلية الزراعة / جامعة البصرةم.د. زينة كاظم عيسى اليونس ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
In this study, essential oils were extracted from Thyme and Star anise using Clevenger method. Oil yield extracted were 2.4% and 4.5% respectively. The physical properties of extracted oils have been studied. Refractive index values ​​for essential oils were 1.4952 and 1.5584 respectively. colors of extracted essential oils were yellow gold and pale yellow respectively, and the taste of Thyme oil was hot burning and the taste of Star anise oil was sweet,as essential oils were dissolved in organic solvents and did not dissolve in water.